2022
DOI: 10.1017/s1368980022002622
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the nutritional status of children under 5 years of age in Guinea between 2005 and 2018

Abstract: Objective: To determine the factors associated with the nutritional status of children under 5 years of age in Guinea between 2005 and 2018. Design: Data from the 2005, 2012 and 2018 Guinea Demographic and Health Surveys (DHS) were used for this study. Three anthropometric indicators (stunting, underweight, wasting) were assessed according to the 2006 WHO Child Growth Standards and analysed according to the year, the characteristics of the household, the child and the mother using multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…In general, stunting was higher in rural areas. Several studies have found a high risk of stunting in rural areas [6][7][8][9][10][11][12][13][14] . According to a national survey, there was a gap between the prevalence of stunting in rural areas (34.9%) and in urban areas (27.3%) 4 , as in East Java.…”
Section: Introductionmentioning
confidence: 99%
“…In general, stunting was higher in rural areas. Several studies have found a high risk of stunting in rural areas [6][7][8][9][10][11][12][13][14] . According to a national survey, there was a gap between the prevalence of stunting in rural areas (34.9%) and in urban areas (27.3%) 4 , as in East Java.…”
Section: Introductionmentioning
confidence: 99%